Accessible AR Framework for Interactive Narratives with Guided Phases - Lasalvia, Paulo; Cruz, Geraldo; Simões, Francisco; Fidalgo, Robson (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais do XXVII Simpósio de Realidade Virtual e Aumentada, 2025)
Augmented Reality (AR) technologies have been increasingly applied in educational and therapeutic contexts, yet they still face important accessibility challenges for users with cognitive impairments. This paper introduces a proposal for an accessible AR framework based on interactive narratives structured in guided phases and supported by multimodal feedback (visual, auditory, and tactile). The goal is to promote digital inclusion and autonomy for users with cognitive disabilities by delivering step-by-step instructions enhanced with narration and other sensory cues. We developed a modular architecture in Unity, integrating plane detection through ARFoundation and distinct modules for phases, audio, and feedback. The system allows therapists to customize activity sequences (narratives) tailored to individual user profiles. We discuss potential use cases in education and rehabilitation, aligning the framework with accessibility guidelines (WCAG) applied to AR. Furthermore, we compare our proposal to related works, highlighting differentiators such as integrated narration, touch-based interaction, modular phase design, and cognitive accessibility focus. Finally, expected results and an initial technical validation with specialists are described, along with future directions for broader applicability.